A multimodal study of smalt preservation and degradation on the painting “Woman doing a Libation or Artemisia” from an anonymous painter of the Fontainebleau School - de Mecquenem, Clément; Eveno, Myriam; Alfeld, Matthias; Pillay, Ruven; Laval, Eric; Ravaud, Elisabeth; Reiche, Ina (European physical journal plus, 2023)
The blue pigment smalt, a synthetic potash glass tinted with cobalt, was widely used between the sixteenth and the eighteenth centuries. As part of a study on the alteration of smalt and the reconstitution of its original color, the painting: Woman doing a Libation or Artemisia (Fontainebleau school, 1570) was examined in which the artist used smalt as a blue pigment, which is now degraded. Noninvasive imaging was performed using macro-2D X-ray fluorescence and reflectance imaging spectroscopy to get an overview of the artist’s palette and its distribution. Samples prepared as cross sections were also analyzed by scanning electron microscopy coupled with energy dispersive spectroscopy, micro-X-ray absorption near-edge structure spectroscopy and synchrotron micro-X-ray diffraction imaging to determine the preservation state of the smalt as well as structural information on other pigments adjacent to smalt grains in individual paint layers, which could play a role in the degradation process. On the one hand, the study conducted on the alteration of smalt has shown that it is very weathered and mixed with hydrocerussite, which could be a factor that would facilitate the alteration. On the other hand, these analyses have made it possible to identify and locate the pigments used, which will be the basis for the virtual reconstruction of the color of the painting.